2018
DOI: 10.1021/acs.jafc.8b00017
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Virtual Screening, Compound Synthesis, and Bioassay for the Design of Chitinase Inhibitors

Abstract: Chitinases play a vital part in the molting phase of insect pests. Inhibiting their activities by the use of drug-like small chemical molecules is thought to be an efficient strategy in pesticide design and development. On the basis of the crystal structure of OfChtI, a chitinase indispensable for the molting of the insect pest Ostrinia furnacalis (Asian corn borer), here we report a chemical fragment and five variant compounds as inhibitors of OfChtI obtained from a library of over 200 000 chemicals by a stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 39 publications
1
48
0
Order By: Relevance
“…Molecular docking is an effective way in drug structure‐based design to generate elementary predictions of the binding modes 60 . In order to verify the possible detoxification mechanism of safener to Zea mays , CSA, compound II‐1 and DKN were respectively docked with Zea mays HPPD (PDB ID: 1SP8), and the theoretical binding mode is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking is an effective way in drug structure‐based design to generate elementary predictions of the binding modes 60 . In order to verify the possible detoxification mechanism of safener to Zea mays , CSA, compound II‐1 and DKN were respectively docked with Zea mays HPPD (PDB ID: 1SP8), and the theoretical binding mode is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another SBVS study to identify Of ChtI inhibitors revealed that the 2-amino-6-methyl-4,5,6,7-tetrahydro-benzo-[ b ]­thiophene-3-carboxylic acid ethyl ester scaffold also inhibited Of ChtI . Several derivatives were synthesized, and the most efficient compound ( 11 ) showed inhibitory activity toward Of ChtI, with a K i value of 1.5 μM.…”
Section: Development Of Small Molecules Targeting Insect Chitinasesmentioning
confidence: 99%
“…Dong et al . screened six candidate compounds from a library of 200 000 compounds using a structure‐based virtual screening approach and reported 2‐(3‐cyclopentylpropanamido)‐6‐methyl‐4,5,6,7‐tetrahydro‐benzo[ b ]thiophene‐3‐carboxylic acid propyl ester among those six candidate compounds to possess the strongest inhibitory activity [27]. However, this compound showed a binding affinity of about −8.76 to −6.96 kcal·mol −1 and it did not show any cancer cell‐killing effects.…”
Section: Discussionmentioning
confidence: 99%